2020
DOI: 10.2118/198646-pa
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Prediction/Inhibition Design Using Machine-Learning Techniques and Probabilistic Approach

Abstract: Summary This paper presents a data-driven methodology to predict calcium carbonate (CaCO3)-scale formation and design its inhibition program in petroleum wells. The proposed methodology integrates and adds to the existing principles of production surveillance, chemistry, machine learning (ML), and probability theory in a comprehensive decision workflow to achieve its purpose. The proposed model was applied on a large and representative field sample to verify its results. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…scenarios using digital siblings, which are copies of the physical asset. Al-Hajri et al (2020) suggested a coupled machine learning and probabilistic models to predict the scale prediction and plan for inhibition. The coupled model was able to predict the scale and quantify the data-driven models' goodness, then quantify the savings.…”
Section: Ai As a Standalone Predictive Toolmentioning
confidence: 99%
“…scenarios using digital siblings, which are copies of the physical asset. Al-Hajri et al (2020) suggested a coupled machine learning and probabilistic models to predict the scale prediction and plan for inhibition. The coupled model was able to predict the scale and quantify the data-driven models' goodness, then quantify the savings.…”
Section: Ai As a Standalone Predictive Toolmentioning
confidence: 99%
“…The data used in the present work was obtained from the open literature as well as our own experiments [4,25,[27][28][29][30]. As explained earlier, the data was collected so as to target three main functionalities minimizing permeability impairment (I), minimizing the possibility of scale damage in the field (II), maximizing oil recovery from matrix (III).…”
Section: Datamentioning
confidence: 99%
“…The nature of the data related to this functionality had been of the categorical type (i.e. TRUE/FALSE), which referred to the occurrence of calcium carbonate scale formation in the field [4]. The data was also more limited than the data in the other two functionalities, in terms of the number of macro-scale parameters enlisted -mostly considering ions data for a practical purpose.…”
Section: Table 4 the Importance Rank Of Influencing Parameters Related To Target Functionality (I) In Sandstone Matrixmentioning
confidence: 99%
See 2 more Smart Citations